1988
DOI: 10.1111/j.1471-4159.1988.tb01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Isatin: Identity with the Purified Endogenous Monoamine Oxidase Inhibitor Tribulin

Abstract: Purified tribulin, an endogenous monoamine oxidase (MAO) inhibitor, has been identified by direct probe insertion mass spectrometry as the indole-2,3-dione, isatin. A gas chromatographic-mass spectrometric assay for isatin has been developed and used to measure its relatively high concentrations in unpurified human urine, and in rat heart and brain. Isatin is a known compound with a broad range of biological activity; this is the first report of its presence in the animal body. Isatin is a potent inhibitor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(102 citation statements)
references
References 12 publications
1
101
0
Order By: Relevance
“…The development of new, safe, and effective agents for the management of cancer is still a challenge. Isatin (1H-indole-2,3-dione) is an endogenous compound in certain organisms and it was discovered in 1988 [2]. It received considerable attention in the medicinal arena because it is included in a number of bioactive heterocyclic compounds with diverse pharmacological profiles [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The development of new, safe, and effective agents for the management of cancer is still a challenge. Isatin (1H-indole-2,3-dione) is an endogenous compound in certain organisms and it was discovered in 1988 [2]. It received considerable attention in the medicinal arena because it is included in a number of bioactive heterocyclic compounds with diverse pharmacological profiles [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…1975;Fowler and Tipton, 1982], Furthermore, MAO inhibition probably is not caused by catecholamine metabolites because MAO is very insensitive to its reaction products [Elsworth et al, 1986]. A recent study has shown that urine extracts from normal human subjects contain the indole derivative, isatin, which potently inhibits MAO B activity [Glover et al, 1988], Although plasma appeared to inhibit platelet and syn aptosomal MAO to a similar extent, there are several drawbacks when comparing the results of MAO activity in synaptosomes and platelets. For example, the plasma and synaptosomes were obtained from two different spe cies, and there is evidence that there are differences between species in brain MAO kinetics and in the intra neuronal to extraneuronal ratios of MAO A and B activi ties [Ross, 1986;Fagervall and Ross.…”
Section: Discussionmentioning
confidence: 99%
“…9 Isatin (2,3-dioxoindole) was the ®rst component of tribulin to be identi®ed, 10 although it is now clear that there are several others. 11 Isatin was originally synthesized in the middle of the nineteenth century and used in dye manufacture and analytical chemistry.…”
Section: Isatinmentioning
confidence: 99%